Hubungan Pengalaman Jatuh Sebelumnya Dengan Takut Jatuh Pada Lansia Di Panti Werdha Surabaya - Anastasia Putu Martha; Raditya Kurniawan Djoar (Jurnal Keperawatan Muhammadiyah, 2018)
Objective:  To analyze the relationship of previous fall experiences with the incident of fear of falling in the elderly living in Panti Werdha Surabaya.Methods:  This research design is analytic observational with cross sectional approach.Results:  Involving 155 elderly living in Panti Werdha Surabaya. Sampling technique using proportional random sampling method. Existing data were analyzed using  Contingency Coefficient Test with significant level of 0.05. The statistical test results obtained results have a previous experience relationship fall with the fear of falling with a correlation value of 0.374 with a significant level of 0.000 (p <0.05)Conclusion:  previous fall experiences have a very meaningful relationship with the fear of falling elderly at Panti Werdha Surabaya.Keywords:  history of falls, fear of falling